Interleukin 28B polymorphism predicts interferon plus ribavirin treatment outcome in patients with hepatitis C virus‐related liver cirrhosis: A multicenter retrospective study in Japan. Issue 9 (9th January 2014) - Shakado, Satoshi; Sakisaka, Shotaro; Okanoue, Takeshi; Chayama, Kazuaki; Izumi, Namiki; Toyoda, Joji; Tanaka, Eiji; Ido, Akio; Takehara, Tetsuo; Yoshioka, Kentaro; Hiasa, Yoichi; Nomura, Hideyuki; et al.
<x xml:space="preserve">Abstract</x> Aim This study evaluated the efficacy of interferon plus ribavirin and examined whether interleukin 28B (IL28B) polymorphism influenced treatment outcome in Japanese patients with hepatitis C virus (HCV)‐related liver cirrhosis (LC). Methods Fourteen collaborating centers provided details of 261 patients with HCV‐related LC undergoing treatment with interferon plus ribavirin. Univariate and multivariate analyses were used to establish which factors predicted treatment outcome. Results Eighty‐four patients (32.2%) achieved a sustained virological response (SVR). SVR rates were 21.6% (41/190) in patients with HCV genotype 1 with high viral load (G1H) and 60.6% (43/71) in patients with non‐G1H. In patients with non‐G1H, treatment outcome was effective irrespective of IL28B polymorphism. In those with G1H, SVR was achieved in 27.1% of patients with the IL28B rs8099917 TT allele compared with 8.8% of those with the TG/GG alleles (P = 0.004). In patients with G1H having TT allele, treatments longer than 48 weeks achieved significantly higher SVR rates than treatments less than 48 weeks (34.6% vs 16.4%, P = 0.042). In patients with G1H having TG/GG alleles, treatments longer than 72 weeks achieved significantly higher SVR rates than treatments less than 72 weeks (37.5% vs 4.1%, P = 0.010). Conclusion Interferon plus ribavirin treatment in Japanese patients with non‐G1H HCV‐related LC was more effective than those with G1H and not influenced by IL28B polymorphism. In those with G1H, IL28B polymorphism may predict SVR and guide treatment duration: SVR rates were higher in those with the TT allele treated for more than 48 weeks and those with the TG/GG alleles treated for more than 72 weeks.